STRATEGI COPING STRESS PADA ORANG TUA YANG MEMILIKI ANAK AUTISME DI PUSAT LAYANAN AUTIS GORONTALO - Lenny Syamsuddin; Salahuddin Liputo; Renaldi Ointu (program studi psikologi, 2024)
This research aims to find out how to deal with stress coping strategies for parents who have children with autism at the Autism Service Center of Gorontalo Province. This research design uses qualitative research with a qualitative descriptive approach. The respondents were parents who had children with autism at the Gorontalo Autism Service Center, there are 4 parents. The findings showed children's tantrums often require parents to be patient, calm and always restrain themselves therefore as not to vent their emotions on their autistic children. It can be concluded the coping strategies for parents who have children with autism is explain 5 aspects, namely social support, positive interpretation, acceptance, rejection and religious aspects. The four respondents were selected based on research characteristics determined by the researcher